If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -12 = 4 + -6x Reorder the terms: -12 + 5x = 4 + -6x Solving -12 + 5x = 4 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -12 + 5x + 6x = 4 + -6x + 6x Combine like terms: 5x + 6x = 11x -12 + 11x = 4 + -6x + 6x Combine like terms: -6x + 6x = 0 -12 + 11x = 4 + 0 -12 + 11x = 4 Add '12' to each side of the equation. -12 + 12 + 11x = 4 + 12 Combine like terms: -12 + 12 = 0 0 + 11x = 4 + 12 11x = 4 + 12 Combine like terms: 4 + 12 = 16 11x = 16 Divide each side by '11'. x = 1.454545455 Simplifying x = 1.454545455
| -2(-3x)=8x+2x | | -37=3-8x | | 19x=49-10 | | 6x-4-3x=20 | | (3a+7)(2a-5)= | | 4x^2+47x+70=0 | | 10(x+.50)=3x+5+7x | | (-19)*y=1900 | | 36x=8x | | 4x+8x=12-10 | | x^3-5x^2+12=0 | | 5+-11n=24 | | (12)(-5)n=0 | | 42=-29(y+5) | | -7(y+4)-6y= | | X^2-7x=-144 | | 2x+x+4+2=3(x+2) | | 49=7f | | b+5=-2b-3 | | 7+2(x-6)=-3+2x(x-1) | | 2(y-4)=-3(y+2)-8 | | x-23=-100 | | 6x^2+3x-135=0 | | -3(-6-2z)=3z | | X^2+7x=-144 | | -24z+17=22 | | (x-4)p(x)=x^2+8x-48 | | 72.4=n+8.9 | | -4xy+3x+6xy-9x+7x= | | x^2-7x=10x | | 4x+y+5z=-9 | | 100(.1)=x |